Is the Number of Missing Teeth Associated With Mortality? A Longitudinal Study Using a National Health Screening Cohort - Kim, So Young; Lee, Chang Ho; Yoo, Dae Myoung; Kwon, Mi Jung; Kim, Ji Hee; Kim, Joo-Hee; Byun, Soo-Hwan; Park, Bumjung; Lee, Hyo-Jeong; Choi, Hyo Geun (Frontiers in Medicine, 2022)
Background: The aim of this study was to estimate the risk of mortality related to the number of missing teeth in a South Korean population. Methods: The ≥ 40-year-old population of the Korean National Health Insurance Service-Health Screening Cohort 2002–2003 was analyzed. Participants were selected from a total of 220,189 participants and included in groups of 0 teeth lost, 1-2 teeth lost, and ≥ 3 teeth lost. Among the total population, 17,211 participants were included in no missing teeth, 1-2 missing teeth, and ≥ 3 missing teeth and were randomly matched 1:1:1 for age and sex. Mortality from specific causes and all-cause mortality were compared among the groups. The hazard ratio (HR) of the number of missing teeth for all-cause mortality or each cause of mortality was analyzed using Cox proportional hazard models. Results: According to the cause of death, the HRs for metabolic disease, digestive disease, and trauma were greater in the group with ≥ 3 missing teeth than in the no missing teeth group. The group with ≥ 3 missing teeth indicated a 1.19-fold higher HR for all-cause mortality than the no missing teeth group (95% confidence intervals [95% CIs] = 1.12-1.27, P < 0.001). The group with 1- 2 missing teeth did not show a higher HR for all-cause mortality. In the group with 1-2 missing teeth, the HRs for mortality from mental disease and digestive disease were higher than those in the no missing teeth group. The group with 1-2 missing teeth did not show a higher HR for all-cause mortality. Conclusions: The number of missing teeth was linked with a higher risk of mortality. For specific causes of mortality, mortality from metabolic disease, digestive disease, and trauma was higher in the participants with the number of missing teeth.